Timber traceability, determining effective methods to combat illegal logging in Africa: A review - Jesugnon Fifamè Murielle Féty Tonouéwa; Samadori Sorotori Honoré Biaou; Eméline Sêssi Pélagie Assèdé; Hippolyte Agossou; Rodrigue O. Balagueman (Trees, Forests and People)
Illegal logging is a leading cause of deforestation and biodiversity loss. Effectively addressing illegal logging is therefore imperative, especially in the African context, which represents the most vulnerable area to deforestation and has fewer certified forests and traceability systems. Timber traceability involves tracking and monitoring species from the forest to their final use, aiming to support low-impact logging and the protection of forest biodiversity. Wood tracking can be planned intentionally from the tree in the forest, either before or during harvesting (prospective method); or it can be used to verify or determine the geographic origin of timber found on the market (retrospective method). Based on a bibliographic search in scopus, the existing literature on timber traceability worldwide was collected to identify those that are being implemented in Africa and those that could contribute to effectively combatting illegal logging in the continent. The most used traceability methods worldwide with useful results are anatomical wood characteristics, DNA methods, forest legislation and certification, marked wooden board surfaces, QR codes, RFID, NIRS, Blockchain and stable isotope ratios.Based on the current situation of African forests, viz. low forest certification rates and low wood traceability (in Africa, on average 5 wood traceability methods have been investigated, of the 24 implemented globally), we propose a wood traceability package (a combination of methods) that includes two retrospective or prospective methods from around the world framed by local forest legislation and considering the socio-economic conditions of the countries. The package will be implemented through a secure integrated online platform supported by policies and monitored by designated competent services. This recommended combination of methods should be enshrined in criminal law. This would help protect African forests, improve their ecological status, and support sustainable forest management.